2011
DOI: 10.35360/njes.240
|View full text |Cite
|
Sign up to set email alerts
|

Themes and theme progression in Swedish advanced learners' writing in English

Abstract: This study investigates how the Themes and Theme progressions in a sample of Swedish advanced learners" writing contribute to the method of development in their texts. A comparison is made to a sample of similar writing by British university students. It was found that the advanced learners" sample contains more interactional Themes, which create a dialogic method of development similar to that found in conversational language. Themes and Theme progressions which are typical of expository writing, on the other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The construction was chosen by the speaker because of its many positive characteristics. In this particular instance, the theme-rheme configuration came first, and then the choice of linguistic constructions was made after that (Herriman, 2011;Nugraha, 2017;Pavavijarn, 2022;Wei, 2015). The function is a deciding factor in the selection process; for example, is there any pressing need to use the construction in order to specifically present the textual theme?…”
Section: Discussionmentioning
confidence: 99%
“…The construction was chosen by the speaker because of its many positive characteristics. In this particular instance, the theme-rheme configuration came first, and then the choice of linguistic constructions was made after that (Herriman, 2011;Nugraha, 2017;Pavavijarn, 2022;Wei, 2015). The function is a deciding factor in the selection process; for example, is there any pressing need to use the construction in order to specifically present the textual theme?…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, the findings from Herriman (2011) and Tåqvist (2016) indicate that Swedish university students of English find it difficult to express themselves with precision in academic texts, and to find the appropriate style using a more colloquial or interactive register than native speakers. Advanced learners would surely benefit from teaching leading to increased awareness of style and register.…”
Section: Research On Learning Teaching and Assessing English And Othe...mentioning
confidence: 97%
“…As mentioned in 2.3.2.1, like in many other parts of the world, scientific publishing in English is commonplace in Swedish higher education and internationalization is synonymous with the use of English. As noted by Herriman (2011) and Tåqvist (2016), notwithstanding the generally high level of English proficiency, there are weaknesses in Swedish students' writing at university level. Also, among postgraduates and researchers, all are not, or do not identify themselves as, fully fledged writers of English, which has been shown by McGrath (2015) and Rosén and Straszer (2017).…”
Section: Writing Skillsmentioning
confidence: 98%
See 1 more Smart Citation
“…Contrastive studies of L2 writing in English have found that some Chinese writers to their detriment use less nominalisation in Theme position in medical papers than English writers (Gao 2012); that some Norwegian writers, influenced by their first language, tend to thematise adverbials (Hasselgård 2009); and that some Swedish writers use more interactional Themes, creating a more dialogic, conversational method of development in texts than English writers (Herriman 2011). This suggests that L2 writers use of Theme can be influenced by the writer's L1 in different respects, and that this can be perceived as detrimental when compared to an academic English norm.…”
Section: Studies Of Theme In L2 Writingmentioning
confidence: 99%